2020
DOI: 10.1186/s12889-020-09181-8
|View full text |Cite
|
Sign up to set email alerts
|

Parental awareness and utilization of meningococcal serogroup B vaccines in the United States

Abstract: Background Meningococcal serogroup B (MenB) is the most common cause of invasive meningococcal disease (IMD) in the United States. The US Advisory Committee on Immunization Practices (ACIP) recommends vaccination of healthy adolescents against MenB based on shared clinical decision-making (Category B recommendation). This survey assessed factors associated with MenB vaccine awareness, utilization, and interest among parents/guardians of US adolescents. Methods Survey pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…A handful of studies performed outside the United States have assessed parents' perceptions about the MenB vaccine and found most parents have heard of meningitis (80-86%) and wanted their child to receive the MenB vaccine (62-64%) [9][10][11][12]. Within the United States, to our knowledge, only two studies examined parents' awareness about and intention for their highschool-aged children to receive the MenB vaccine [13,14]. Among a 2017 convenience sample of 445 parents of Minnesota high school students, 72% had heard of meningitis, but only 20% were aware of the MenB vaccine [13].…”
Section: ]mentioning
confidence: 99%
See 1 more Smart Citation
“…A handful of studies performed outside the United States have assessed parents' perceptions about the MenB vaccine and found most parents have heard of meningitis (80-86%) and wanted their child to receive the MenB vaccine (62-64%) [9][10][11][12]. Within the United States, to our knowledge, only two studies examined parents' awareness about and intention for their highschool-aged children to receive the MenB vaccine [13,14]. Among a 2017 convenience sample of 445 parents of Minnesota high school students, 72% had heard of meningitis, but only 20% were aware of the MenB vaccine [13].…”
Section: ]mentioning
confidence: 99%
“…In this study, compared to parents who had not heard of the vaccine, the odds of parents’ intent to have their child vaccinated increased nearly fourfold among parents aware of the MenB vaccine and threefold among parents at least somewhat concerned about meningitis. A second study included a random sample of 619 parents across the US, and weighted results to correspond with the US population [ 14 ]. Based on the weighted results, an estimated 43% of US parents are aware of the MenB vaccine, and among those only 45% intend to get the MenB vaccine.…”
mentioning
confidence: 99%
“…Several studies have shown that there is a lack of meningococcal disease and meningococcal vaccine knowledge among parents [ 12 , 18 , 51 , 52 , 53 , 54 ]. This lack of awareness has resulted in disparities in meningococcal vaccination rates among those in the 10- to 23-year age range.…”
Section: Resultsmentioning
confidence: 99%
“… 30 In another study, the authors detail the importance of one-on one discussion to build trust, create awareness, and increase uptake of vaccination amongst the minority group. 31 It is important to emphasize the central role policies and vaccine rationing play in ensuring that disadvantaged communities are given precedence during country-wide vaccination measures.…”
Section: Discussionmentioning
confidence: 99%